PENGARUH KUALITAS PRODUK, KUALITAS LAYANAN, DAN CITRA MEREK TERHADAP LOYALITAS NASABAH YANG DIMEDIASI OLEH KEPUASAN NASABAH (Studi pada Nasabah PT. BRI (Persero) Tbk. Yogyakarta) - Afriani, Lita Ningrum; Setyono, Hendro (Jurnal Fokus Manajemen Bisnis, 2017)
For companies, loyal customers mean a lot besides illustrates the amount of profitability obtained by loyal consumers can also show the image or image of the company in the public eye. Loyal customers can become partners in developing new products, because they maintain and defend and even use the services of existing companies. According to Darsono (2004) a loyal customer becomes a valuable asset for the company. Loyal customers will reduce the effort to find new customers, giving positive feedback to the company. Companies must be able to satisfy old customers and create new customers, if you want to win the competition. PT. BRI (Persero) Tbk. Yogyakarta must be able to answer the existing competition challenges. The population in this study are customers of Bank Rakyat Indonesia Yogyakarta and have been customers for at least one year. While the sample in this study is a portion of the number of customers from BRI Bank Yogyakarta. The sampling technique uses accidental sampling and purposive sampling. While the data used in the study are primary data, that is data obtained directly from respondents by the researchers themselves through questionnaires. Analysis tools using multiple linear regression The results of the analysis can be concluded that: Product quality has a significant effect on customer satisfaction. Service quality has a significant effect on customer satisfaction. Brand image does not significantly influence customer satisfaction. Product quality, service quality and brand image together significantly influence customer satisfaction. Product quality does not significantly influence customer loyalty. Service quality has a significant effect on customer loyalty. Brand image does not significantly influence customer loyalty. Product quality, service quality and brand image together significantly influence customer loyalty. Customer satisfaction significantly influences customer loyalty. Customer satisfaction mediates the effect of product quality on customer loyalty. Customer satisfaction does not mediate the effect of service quality on customer loyalty. Customer satisfaction does not mediate the effect of brand image on loyalty the customer.